Sustainable home gardens in Western Kenya: a qualitative study for co-designing nutrition-sensitive interventions - Hansen, Lea-Sophie; Kihagi, Grace Wothaya; Agure, Erick; Muok, Erick M. O.; Mank, Isabel; Danquah, Ina; Sorgho, Raissa (Journal of rural studies, 2023)
Populations living in rural sub-Saharan Africa (SSA) increasingly face negative climate change impacts on their nutrition and health status. For smallholder farming families, home gardens can serve as an adaptation strategy, by offsetting climate change-related harvest losses and diversifying households' diets. The present study aimed to identify perceptions and experiences among rural caregivers of children under five years and local stakeholders working in the fields of agriculture or nutrition with regard to home gardening in Siaya County, Kenya. Thirty in-depth interviews with caregivers of young children and 26 interviews with local stakeholders were conducted, using a semi-structured interview guide. The data were analysed employing inductive content analysis. Caregivers and local stakeholders perceived home gardens as beneficial for the households’ nutrition, finances, and women empowerment. However, they also pointed to five major challenges in the process of establishing and maintaining home gardens: 1) water scarcity, 2) limited financial capital, 3) demanding physical labour, 4) limited land availability/control, and 5) lack of knowledge and technical support. For the design of sustainable home gardens, we identified four components as essential at the implementation stage: 1) locally available material and resources, 2) strong community collaboration and co-design, 3) comprehensive capacity building, 4) and lasting local partnerships. In conclusion, the establishment and sustained management of home gardens in Siaya County require a holistic, participatory and multi-actor approach. This will facilitate the provision of essential inputs and activities to ensure a sense of ownership and responsibility.